Addressing The Importance of Financed Emissions to The Indonesian Financial Sector - Rizky, Muhammad; Firmansyah, Amrie (Research Synergy Foundation, 2024)
Business trends, including the disclosure of financed emissions, drive more precise sustainability reporting. Financed emissions are greenhouse gas emissions from activities or projects sponsored by financial institutions, such as banks, insurance firms, pension funds, and other financial institutions. This concept emerges from an examination of the function of a financial service institution in distributing capital to companies that emit emissions or have a high carbon footprint. This study aims to examine the phenomenon of financed emissions and formulate policy recommendations to disclose financed emissions in Indonesia. Employing a systematic literature review approach, this study discovered various emission accounting standards, including the GHG Protocol, PCAF, and new standards developed by the ISSB and TCFD. The issuance of green bond instruments, sustainable loans, and the formation of carbon exchanges all contribute to Indonesia’s emission accounting reporting regime. Policy recommendations include the development of environmentally sound KYC policies for financial services institutions, the synchronization of business classification according to the Green Taxonomy or KUBL, and proposals for investment emission intensity taxation in Indonesia. However, hurdles to financed emission disclosure include data quality, complexity of the finance transaction structure's complexity, the technology's equivalency, and incomplete standard setting.